2020
DOI: 10.3390/ma14010167
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Three Manufacturing Techniques for Sustainable Porous Clay Ceramics

Abstract: This study proposes different manufacturing techniques (manual pelletization, powder pressing, and “shell scaffold”) to obtain lightweight clay ceramics containing recovery raw materials. The sintering in an electrical furnace (1000 °C, 1 h processing time) was conducted by traditional firing from room temperature, for pressed and shell-scaffold samples, while the flash heating (i.e., samples directly put at 1000 °C) was used only for the pellets. The porous materials (porosity 40–80%), functionalized with nut… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 26 publications
0
5
0
Order By: Relevance
“…Pelleting is a form of aggregation that allows the particle size to increase. In the pharmaceutical, food and fertilizer industries, it is used to transform hundreds of compounds from fine powders into manageable particles [19]. As a result, it is strong enough to handle and withstand the special application of sintered raw materials during firing, but still provides nutrients when needed.…”
Section: Manufacturing Methods By Firing Processmentioning
confidence: 99%
“…Pelleting is a form of aggregation that allows the particle size to increase. In the pharmaceutical, food and fertilizer industries, it is used to transform hundreds of compounds from fine powders into manageable particles [19]. As a result, it is strong enough to handle and withstand the special application of sintered raw materials during firing, but still provides nutrients when needed.…”
Section: Manufacturing Methods By Firing Processmentioning
confidence: 99%
“…Table II summarizes the properties of some porous ceramic materials that were obtained from the use of organic waste as porogenic agents. The data reveal that ceramic bodies with a high level of porosity, low thermal conductivity, and satisfactory mechanical strength can be obtained from waste such as rice husks [12], banana leaves [13], olive stones [14], wheat straw [14], yeast [15] and coffee waste [16,72]. Additionally, it is observed that the most porous ceramic materials produced using organic waste in their composition are applied in the civil construction industry, such as porous clay bricks and foams for thermal and/or acoustic insulation.…”
Section: Organic Wastementioning
confidence: 99%
“…Different processing techniques of cellular ceramics include gel casting, replication of a sacrificial foam template, direct foaming of a liquid slurry, burn-out of fugitive pore formers, among others [11,12]. Andreola et al [13] experimented three different manufacturing techniques of porous ceramics and concluded that one technique can be preferable as compared to the others depending on the specific use. The pore-former technique is based on the mixing of the ceramic powder, or its precursors, with a fugitive material that acts as a poreforming agent, followed by the formation of a green body, extraction of the pore-former, and sintering of the ceramic phase [14].…”
Section: Evaluating the Properties Of Cellular Ceramics Prepared With A Granite Dust And Plantain (Musa Paradisiaca) Peel Powder For Extementioning
confidence: 99%